The cultural evolution of pluralistic ignorance - Sergey Gavrilets; Johannes Karl; Michele J. Gelfand (Proceedings of the National Academy of Sciences, 2026)
Pluralistic ignorance—the systematic misperception of others’ attitudes—can entrench suboptimal norms, yet its dynamics remain poorly understood. We develop a mathematical model of the coevolution of actions, private attitudes, and beliefs about others, with societal tightness as a central parameter. Our framework integrates theories of spirals of silence, preference falsification, and cultural mismatch into a single dynamic system capturing the effects of material payoffs, cognitive forces, and social influence. The model shows that pluralistic ignorance can arise from lags between attitude change and belief updating, even without silence or deception. Dynamics unfold faster in loose cultures and slower in tight ones: loose societies display sharp but transient peaks of pluralistic ignorance, while tight societies sustain slower, persistent mismatches. Both can experience cultural evolutionary mismatch but through distinct pathways—internalized norm adherence in loose cultures vs. conformity pressure in tight ones. These mechanisms may help explain global patterns where private support exceeds perceived support, such as climate action, women’s rights, and abortion attitudes. Interventions must therefore be culturally tailored: accelerating attitude change through highlighting benefits is effective in loose cultures, whereas lowering expression costs (via anonymity or legal protections) empowers norm entrepreneurs in tight cultures. Our framework identifies policy levers and clarifies when apparent opinion stability conceals underlying shifts, offering insights for democratic societies navigating rapid social change.